2016
DOI: 10.1139/cjpp-2015-0322
|View full text |Cite
|
Sign up to set email alerts
|

The effects of motor rehabilitation training on clinical symptoms and serum BDNF levels in Parkinson’s disease subjects

Abstract: Keyword:https://mc06.manuscriptcentral.com/cjpp-pubs Moreover, parallel treatments in animals up-regulate brain-derived neurotrophic factor (BDNF). Thus, we investigated the effect of a motor rehabilitation protocol on PD symptoms and BDNF serum levels.Motor rehabilitation training consisted of a cycle of 20 days/month of physiotherapy divided in three daily sessions. Clinical data were collected at the beginning, at the end and at 90 days follow-up.BDNF serum levels were detected by ELISA at 0, 7, 14, 21, 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 56 publications
2
43
0
2
Order By: Relevance
“…Furthermore, it has been demonstrated that exercise protects dopaminergic neurons of the substantia nigra pars compacta from neurotoxicity, and a mechanism proposed to account for this neuroprotection is the upregulation of neurotrophic factors, as BDNF [43]. Decreased BDNF levels are associated with cognitive deficits in PD patients, and motor rehabilitation, besides improving PD symptoms, also increases BDNF levels [44, 45], supporting our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, it has been demonstrated that exercise protects dopaminergic neurons of the substantia nigra pars compacta from neurotoxicity, and a mechanism proposed to account for this neuroprotection is the upregulation of neurotrophic factors, as BDNF [43]. Decreased BDNF levels are associated with cognitive deficits in PD patients, and motor rehabilitation, besides improving PD symptoms, also increases BDNF levels [44, 45], supporting our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Research has shown that in cerebral ischemic rats BDNF/TrkB expression is upregulated to stabilize ischemia-induced Ca 2+ imbalance, inhibit the toxic effect of excitatory amino acids on neurons, and stimulate the survival and regeneration of damaged neurons as well as differentiation and proliferation of neural stem cells [2426]. Rehabilitation training has been found to increase the expression of BDNF in cerebral ischemia mice [27] and in the serum of patients with Parkinson's disease [28]. On the other hand, resveratrol is shown to increase the expression of Sirt1 as well as BDNF and its receptor TrkB [29] in elderly rats, suggesting that Sirt1 might protect retinal neurons and visual function through the regulation of BDNF/TrkB.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies using blood sampling methods [27,28,33] showed positive results on neuroplasticity after a period of physical exercise. However, a fourth study within the neurochemical domain, Angelucci et al, showed no effects [31]. In the seven studies in which brain function was the main outcome measure, five different methods showed positive effects on neuroplasticity.…”
Section: Studymentioning
confidence: 98%
“…Six studies included participants according to disease stage based on the Hoehn and Yahr scale [25,[28][29][30][31][32] (see Table 1 for study characteristics).…”
Section: Neural Plasticitymentioning
confidence: 99%
See 1 more Smart Citation